Effect of Artificial Salvia on Force Values of Two Types of Nickel Titanium Ortho-dontic Arch Wires - Afrah K Al -Hamadani; Enas T Al-Jwary (University of Mosul, College of Dentistry, 2012)
Aims: To study the effect of artificial saliva and time interval on the amount of force values of nitinol and superelastic NiTi wires. Materials and Methods: Two types of orthodontic wires chosen for the study nitinol and superelastic NiTi wires of a guage of 0.016 inch in diameter (Dentaurum, Germany). Specimens of the wires were divided in to two groups ;the control group(dry condition) contained the wires as - received condition and experimental groups for the study of the force value of wires which subjected to artificial saliva for three time incubation periods (3 days, 7 days, 28 days) . At end of each incubation periods ,the wire specimens were tested for the effect of artificial saliva on force values of the wire. The measurement of force values of arch wires done with a universal tensile testing ma-chine ,the force values of specimens were evaluated with the help of three point bending test. The re-sults were subjected to the descriptive statistics and to the ANOVA and Duncan's Multiple Range Analysis Tests to detect the amount of changes among these groups . Result: The findings of the present study showed that the control group of nitinol wires had the highest rate of force value with significant difference (P≤ 0.05) with experimental groups, while the experimental group after 28 days gave rise to the lowest one with significant difference (P≤ 0.05) from other groups. For the superelastic nickel titanium the result showed that the control group had the highest rate of force value while the experimental group after 28 days gave rise to the lowest one with significant difference (P≤ 0.05) from control and non significant difference (P> 0.05) with the experimental groups after 3 days and 7 days. Conclusion: The nitinol wires showed a continuous change in force values with increase time in ar-tificial saliva, so this required reactivating or changing the wire at a certain interval of use. While force values of the superelastic nickel titanium wires decreased after 3 days interval and remained constant after that .